Le biomimétisme des espèces marines en industrie innovatrice - CHENINE, OUASSIM (My University, 2024)
Awareness of the fight against marine pollution is relatively recent. First of all, the Algerian marine and coastal environment is very rich in natural resources. It offers significant opportunities for coastal populations in terms of livelihoods. However, this environment is confronted with many problems: coastal erosion, overexploitation of biological and abiotic resources, marine and coastal pollution. Thus, the country's main challenge is to ensure the optimal conservation of this environment. This is the direction of our project, which is developing an innovative device inspired by sea sponges to create an artificial environment for sea creatures. Using state-of-the-art 3D design technologies and a limestone sedimentation process, it offers a semi-natural and durable structure. The device incorporates a pollution detector, to measure variables such as pH and temperature, with a simple light system (green for clean, red for polluted). Its design and underwater lighting add an attractive visual dimension. This project combines biomimicry and technological innovations to improve the monitoring and preservation of marine ecosystems.
Keywords: Biomimicry, sea sponge, monitoring, preservation